History of wine tourism in Serbia - Maksimović, Mirjana; Pivac, Tatjana; Đorđević, Jasmina (Turizam, 2021)
With regard to the history of wine tourism, all recent literature has presented it as a young branch of tourism that has been developing intensively at the end of the 20th century. It is believed that the roots of wine tourism originate from France, while the first commercial wine tours were organized in California. When it comes to Serbia, few researches point out that wine tourism has been developing since the 1990s, and that the pioneers of that endeavour are two wineries in Sumadija: Aleksandrovic and Radovanovic. However, historical facts show otherwise. Wine tourism has existed in Serbia for more than 120 years, while its beginnings go back more than 155 years. This paper, created by researching the route of the Constantinople Wine Route, is an overview of currently available historical material that proves the above mentioned and it is the first of its kind in Serbia. More precisely, this paper presents the first written history of wine tourism in Serbia.
Keywords: History of wine tourism in Serbia, Constantinople Wine Route, Serbian Wine Tourism Day